Cover Feature: Structural, Morphological and Interfacial Investigation of H2V3O8 upon Mg2+ Intercalation (Batteries & Supercaps 4/2023). Issue 4 (23rd March 2023) - Surace, Yuri; Romio, Martina; Amores, Marco; Hamid, Raad; Cupid, Damian; Sauer, Markus; Foelske, Annette; Jahn, Marcus
Abstract : The Cover Feature shows the different phenomena occurring when cycling H2 V3 O8, a promising cathode material for Mg‐ion batteries, in TFSI‐based electrolytes. Post‐mortem analysis showed evidence of Mg trapping into the crystal structure, formation of a cathode electrolyte interphase (CEI) containing TFSI ions and MgF2, and vanadium dissolution into the electrolyte. More information can be found in the Research Article by Y. Surace and co‐workers .